Analysis of synthesized doped vertical silicon nanowire arrays for effective sensing of nitrogen dioxide: As gas sensors - Kashyap, Vikas; Pawar, Hariom; Kumar, Chandra; Chaudhary, Neeru; Saxena, Kapil (Frontiers in Materials, 2022)
In the present study, the controllable fabrication of silicon nanowires (Si NWs) with vertical alignment was accomplished using metal assisted chemical etching (MACE). The different characteristics, such as structural, morphological, chemical, optical, and dielectric properties were analyzed using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), Raman spectroscopy, ultraviolet-visible diffuse reflectance spectroscopy (UV-DRS), and LCR [inductance (L), capacitance (C), and resistance (R)] meter (volume of the gas-sensing chamber is 650 mm3). It was revealed from the morphological study i.e., from the FESEM that p-type Si NWs are smaller in size than n-type Si NWs which is attributable to the energy band gap. The optical band gap (Eg) is observed to increase from 1.64 to 1.89 eV with the decreasing of the crystallite size and the optical reflection spectra of the Si NWs show a shift toward a lower wavelength (blue shift). Moreover, Raman spectra verified the red-shifted, asymmetrically broadened Raman line-shapes, which provides information about the size confinement effect in Si NWs. The MACE approach is excellent for synthesizing nanowire structures for use in gas-sensing applications due to its flexibility. The sensitivity of synthesized Si NWs was tested for NO2 gas. The sensor method is unique based on the testing of the device in the presence of a test gas because the use of the gas-sensing setup has the potential to measure the change in resistance by varying frequency, temperature, and time.